Nurses' Advocacy Behaviors in End-of-Life Nursing Care - Thacker, Karen S (Nursing ethics, 2008)
Nursing professionals are in key positions to support end-of-life decisions and to advocate for patients and families across all health care settings. Advocacy has been identified as the common thread of quality end-of-life nursing care. The purpose of this comparative descriptive study was to reveal acute care nurses' perceptions of advocacy behaviors in end-of-life nursing practice. The 317 participating nurses reported frequent contact with dying patients despite modest exposure to end-of-life education. This study did not confirm an overall difference in advocacy behaviors among novice, experienced and expert nurses; however, it offered insight into the supports and barriers nurses at different skill levels experienced in their practice of advocacy.